Percutaneous Fixation by Internal Cemented Screw for the Treatment of Unstable Osseous Disease in Cancer Patients - Deschamps, Frederic; Yevich, Steven; Gravel, Guillaume; Roux, Charles; Hakime, Antoine; de Baère, Thierry; Tselikas, Lambros (Seminars in Interventional Radiology, 2018)
Interventional radiology expertise in image guidance has expanded the treatment options for cancer patients with unstable osseous disease. Percutaneous fixation by internal cemented screw (FICS) describes the technique by which the interventional radiologist stabilizes a fracture or impending fracture with the percutaneous placement of a cannulated screw that is locked in position by polymethyl methacrylate cement. The durable metallic screws provide added resistance to torque and tension stresses that complement the axial compression resistance of cement. Compared with cementoplasty alone, the procedure has been advanced as a more durable and precise technique for stabilization of osseous disease for certain disease presentations in cancer patients. The application of advanced image guidance techniques improves upon existing percutaneous surgical techniques to facilitate approaches that would otherwise prove quite challenging, particularly with stabilization of the pelvic flat bones. This article examines the applications of percutaneous FICS procedures for the treatment of unstable osseous disease in cancer patients. Indications, techniques, and follow-up care are reviewed. Case examples in which FICS can be performed in unstable pathology are detailed.
Keywords: bone fracture; pain palliation; cement consolidation; screw fixation; cementoplasty; interventional radiology